Respresentasi Emosi Melalui Gestur dan Ekspresi Wajah dalam Film Miracle in Cell No. 7 Versi Indonesia (Analisis Pragmatik) - Cantika, Norika Parlinda; Anhar; Asyura, Irna; Juniar, Aulia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The representation of emotions in the study of communication, through gestures and facial expressions plays an important role because these elements can enrich the understanding of the characters and storyline. This study aims to identify and analyze the various types of gestures and facial expressions that appear in the film Miracle in Cell No. 7 and their influence in building emotional depth, enriching the audience's experience, and creating an emotional bond between the characters and the audience. The method used is qualitative analysis with a pragmatic approach, where data is collected through re-enactments of key scenes that show non-verbal communication. Data analysis was carried out in a qualitative descriptive manner by classifying gestures and facial expressions based on the types of emotions represented such as joy, sadness, and anger. The results of the study showed that gestures and facial expressions significantly strengthened the verbal narrative and created a deeper emotional experience for the audience. These findings contribute to the study of non-verbal communication and Indonesian cinema and provide new insights into the understanding of emotional representation through film media